Rvhe Nagāʺ Taṅʻ Vaṅʻʺ e* Cakʻ mhu cuikʻ pyuiʺ tacʻ lhamʻʺ tuiʺ - Taṅʻ Vaṅʻʺ, Rvhe Nagāʺ (Canʻʺ Canʻʺ mhu Lakʻ mhu Lupʻ ṅanʻʺ Samavāyama ʼA saṅʻʺ, 1994)
Agricultural machineries, indigenously developed and manufactured by the San San Industrial Co-operative Society, Rangoon, Burma.